CASES - AS METHODS OF PREPARING STUDENTS FOR THE RATIONAL ORGANIZATION OF WORK (Intent Research Scientific Journal, 2023)
This article discusses the positive effect of case studies in teaching students the correct and effective organization of pedagogical work, several cases are given.